DISTURBANCE OF CIRCADIAN RHYTHM AS A CHARACTERISTICAL DEPRESSION SYMPTOM - Md. Jahangir Alam (International Journal of Multidisciplinary Research and Studies, 2021)
Internal expressions of the solar day, known as circadian rhythms, are what make it possible for organisms to adjust to changes in the environment that are predictable across time. These about 24-hour rhythms are regulated by molecular clockworks that are housed inside the brain. These clockworks are set back to exactly 24 hours on a daily basis when they are exposed to the light–dark cycle. Through both humoral and neuronal communication, the mammalian hypothalamus, which houses the "master clock," transmits information about the passage of time to the rest of the body. There is a connection between mood disorders and circadian rhythms, and this connection goes in both directions. Mood disorders are frequently linked to disturbances in the circadian clock-controlled responses of the body, such as sleep and cortisol secretion.